Enhancing Fourth-Grade Students’ Mathematics Achievement through Wordwall-Based Teaching at the Right Level (TaRL): A Classroom Action Research Study - Khafidhoh, Alfi Nur; Ambarwati, Adna Arum; I Ketut Suastika (Prodi Pendidikan Matematika Universitas Pesantren Tinggi Darul Ulum Jombang, 2025)
Mathematics remains a challenge for most children. The difficulty in understanding abstract concepts and applying them in practice often results in declining student learning outcomes, especially in subjects that require conceptual understanding and unit conversion, such as volume measurement. This study aims to improve mathematics learning outcomes among fourth-grade elementary school students through the application of the Teaching at the Right Level (TaRL) strategy. This research employed a Classroom Action Research (CAR) design, which consisted of two cycles. Each cycle comprised four stages: planning, implementation, observation, and reflection. The participants were 28 students from SDN Tanjungrejo 2 Malang. The findings showed that the proportion of students achieving the success criteria increased from 43% to 89%, with an average score of 86. The application of the TaRL strategy, supported by Wordwall media, proved effective in improving students’ mathematics learning outcomes.